Implementasi Pendidikan dan Kesadaran Terhadap Lingkungan Hidup: (Studi Kasus di SMAN 5 Karawang) - Suhud; Hilman Mauludin; Akhmad Roziqin (Indonesian Journal of Islamic Education Studies (INJURIES), 2025)
This study aims to analyze the implementation of environmental education and awareness at SMAN 5 Karawang. The research uses a qualitative approach with a case study method, involving interviews, observations, and questionnaires to gather data from 50 students and 10 teachers. The results indicate that environmental education has been integrated into the school curriculum through various programs, such as tree planting and waste management campaigns. However, the level of environmental awareness among students is still moderate, with only 50% of students applying their knowledge in daily life. The study concludes that while the implementation of environmental education is good, increasing student participation and strengthening their environmental consciousness are necessary for more effective outcomes. Keywords: Environmental Education; Environmental Awareness; Student Participation